2010
DOI: 10.1111/j.1365-3040.2010.02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil [N] modulates soil C cycling in CO2‐fumigated tree stands: a meta‐analysis

Abstract: Under elevated atmospheric CO(2) concentrations, soil carbon (C) inputs are typically enhanced, suggesting larger soil C sequestration potential. However, soil C losses also increase and progressive nitrogen (N) limitation to plant growth may reduce the CO(2) effect on soil C inputs with time. We compiled a data set from 131 manipulation experiments, and used meta-analysis to test the hypotheses that: (1) elevated atmospheric CO(2) stimulates soil C inputs more than C losses, resulting in increasing soil C sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 64 publications
4
68
1
Order By: Relevance
“…The increase in N tot is a possible consequence of eutrophication. The increase in C org is a possible consequence of humus restoration (Dieleman et al 2010). The slight trend of increase in the content of C org indicated that it might refer to a reliable medium-term prediction but repeated occurrence of unusual values due to the uncertain quality of sampling probably influenced the reduction of the probable development prediction length to five years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in N tot is a possible consequence of eutrophication. The increase in C org is a possible consequence of humus restoration (Dieleman et al 2010). The slight trend of increase in the content of C org indicated that it might refer to a reliable medium-term prediction but repeated occurrence of unusual values due to the uncertain quality of sampling probably influenced the reduction of the probable development prediction length to five years.…”
Section: Discussionmentioning
confidence: 99%
“…Fluctuations in soil carbon cycles mainly occur due to changes in the balance between above-ground and underground resources (Wang et al 2012). Nevertheless, to specifically estimate soil property changes requires the formulation of models that assume the influence and synergy of both acid deposition and climatic changes (Dieleman et al 2010).…”
mentioning
confidence: 99%
“…Indeed Luyssaert et al (2010) suggested that forests continue to sequester carbon in spite of intensive harvesting of wood since growth has outpaced losses from harvesting and heterotrophic respiration. This increase in growth has been attributed to a large fraction of young productive trees (Nabuurs et al, 2003), changes in management and increase in forest area (Ciais et al, 2008), increased CO 2 (Friedlingstein et al, 1995) and temperature (Myneni et al, 1997).…”
Section: Biogeochemistry Of European Forestsmentioning
confidence: 99%
“…However, the fertilization effect of CO 2 may be limited by the progressive scarcity of nutrient supplies, especially N (Reich et al 2006;Dieleman et al 2010) or by a lack of positive growth response despite the stimulation of the C assimilation rate induced by CO 2 (Körner 2006;Kirschbaum 2011). Additionally, in natural conditions, the response of an individual can depend on the identity of neighboring species (Lau et al 2010) because processes affecting growth, such as nutrient acquisition, can be contingent on the identity of neighboring species under enhanced levels of CO 2 (Friend et al 2000;Zak et al 2012).…”
Section: Introductionmentioning
confidence: 99%